Aneurysmal bone cyst of the mandible: Report of a case with a review of the literature - Hasan Onur Simsek; Derya Yildirim; Ozlem Gormez; Esra Yuce; Fatma Nilgun Kapucuoglu (Wolters Kluwer Medknow Publications, 2014)
Aneurysmal bone cyst (ABC), is a rare benign osteolytic bone neoplasm of bone tissue characterized by several sponge-like blood or serum filled, generally non-endothelialized spaces of various diameters that can contain osteoid tissue and osteoclast-like giant cells. In this article, we describe a case of ABC in the mandibular corpus region with clinical, radiological and pathological findings and review the literature concerning the case. A 23-year-old male patient attended to our clinic with the complaint of a mild-pain on the left posterior lower jaw since two months. The superior margin of the lesion was extending between the apical third parts of the roots of the teeth 35-38. Cone beam computed tomography (CBCT) was performed. CBCT Slices revealed an expansile lesion with hydraulic-appearing outer margins above the mandibular canal. Excisional surgical treatment was performed after raising a mucoperiosteal flap and finalized with curette of lesion under local anesthesia. Diagnosis of aneurysmal bone cyst was confirmed by histopathological evaluation. The patient was pain free after six months follow-up, and panoramic radiography showed no evidence of recurrence. The ABC is most common in those regions of the skeleton where there is a relatively high venous pressure and high marrow content. Clinical presentation of the ABC varies from a small, indolent, asymptomatic lesion to rapidly growing, expansile, destructive lesion causing pain, swelling, deformity, neurologic symptoms, pathologic fracture, and perforation of the cortex. As the radiologic and clinical presentation of ABC is extremely variable, histopathologic examination is placed a great emphasis on for the diagnosis.